(untitled) (Islamic Sciences Journal, 2023)
The enemies of Islam, in the past and present, used to direct their accusations against our great Islamic religion, using various methods and ways to question the validity of the Prophet’s Sunnah and to challenge its narrators. This research came to respond to the appellants and skeptics of the Islam’s narrator the great companion of the Prophet Abu-Huraira (may Allah be pleased with him) and refute their fabrications and accusations against him that he took knowledge from Judaism and Christianity through his narration of the Israʼiliyyat. For Ka`b Al-Ahbar, Basrah Al-Ghafari, and Abdullah bin Salam, and their reference is the hadith that he narrated about the Merit of Friday, in which he went out to the Tuor (mountain) and his meeting with Ka`b Al-Ahbar, so they raised many suspicions, doubts and questions about this hadith, I studied them extensively and responded to all their fabrications and allegations as a sober scientific response and showed the invalidity and nullity of this Suspicion.